Kontribusi Sosial Program MBKM Pertukaran Mahasiswa Merdeka dalam Pemberdayaan Masyarakat Pesisir di Pulau Setokok Batam - Wisnu Yuwono; Agung Wibowo; Siswuri Andari; Leni Mardayanti; Munaroh Susanto; Andi Putri Isnayani Kamal; Frendelina N. Nesimnasi; Supriadi Supriadi; Asya Ian Ramadani; Nurhayati Balqis (Social Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) have played an important role in the economy of developing countries such as Indonesia, which have potential natural resources. One of them is the Fish of Tamban Menari on Setokok Island, Batam City, Riau Islands which has become a highly marketable processed product. The main obstacle to this product marketing process is still conventional. In social contribution activities to the community, authors use the mentoring method in developing, expanding, and applying science and technology for development, through increasing the ability of human resources to handle and solve problems faced by partners. The results of this activity indicate an increase in the ability and skills of the community, especially in utilizing social media as a very effective alternative marketing medium for increasing branding and sales.